The Learning Institute: Promoting Social Justice Advocacy Within a Continuing Education Program. Issue 4 (7th August 2016) - Rice, Karen; Girvin, Heather; Frank, Jennifer; Foels, Leonora
ABSTRACT: The pursuit of social justice is an overarching framework that defines the social work profession. The goals of macro social work practice are centered on issues of social justice with strategies that include changing community conditions and creating a sense of solidarity, with particular emphasis on broadening the opportunities for marginalized populations. Given the natural alignment between social justice and macro social work practice, the exclusion of macro practice content in educational experiences should concern social workers and educators alike. The Learning Institute emerged in large part from a school's shared concern with the micro/macro dichotomy that often characterizes the profession, as well as the faculty's commitment to renewing the profession's dedication to our social justice mandate. Results from this formative assessment clearly suggest that participants in the Learning Institute series may have experienced bifurcated education, exposure, and training to social justice advocacy on the macrolevel. Implications for future research and continuing education are discussed.